Consideraciones sobre la Gerencia Universitaria en la Escuela de Economía de la Facultad de Ciencias Económicas y Sociales de la Universidad de Los Andes. - Monagas, Dulce (SABER ULA, 2006)
SUMARIO Editorial Morillo Moreno, Marysela C. Ideas para Impulsar la Investigación en la Facultad de Ciencias Económicas y Sociales de la Universidad de Los Andes (FACES-ULA). Ideas design to stimulate the investigation in the Faculty of Economic and Social Faculty Sciences of the University of The Andes. Casal, Rosa Aura Cambio de Paradigmas, Complejidad y Educación: Breves comentarios para fundar un debate. Change of Paradigms, Complexity and Education: Some commentaries to found debate. Ferguson, Alex Nuevas Técnicas de Control y Gestión de Costos en Búsqueda de Competitividad. New Technologies of Control and Management of Costs in Search of Competitiveness. Molina de Paredes, Olga Rosa Consideraciones sobre la Gerencia Universitaria en la Escuela de Economía de la Facultad de Ciencias Económicas y Sociales de la Universidad de Los Andes. Considerations on the University Management in the School of Economy of the Faculty of Economic and Social Sciences of the University of The Andes. Monagas, Dulce La Contabilidad de Costos y el Diseño de Mezcla de Productos. The Accounting of Costs and the Design of Mixture(Mixing) of Products. Morillo Moreno, Marysela C. Internet y las Comunicaciones Corporativas: Reorientando la Información Financiera de las Empresas. Internet and the Corporate Communications: Reorientating the Financial Information of the Companies. Santaella, Germán La Universidad de Los Andes como Organización Inteligente. The University of The Andes like Intelligent Organization. Viloria O., Norka Eventos
Considerations on the University Management in the School of Economy of the Faculty of Economic and Social Sciences of the University of The Andes.
Keywords: Sociedad del conocimiento; Gerencia; Universidad; Ineficiencia; Departamento de Contabilidad y Finanzas; Escuela de Economía; Facultad de Ciencias Económicas y Sociales; Knowledge society; Management; University; School of economies; Inefficacy; Revista Actualidad Contable FACES; Revistas